2004
DOI: 10.1088/0031-9155/49/14/020
|View full text |Cite
|
Sign up to set email alerts
|

Choice of the regularization parameter for perfusion quantification with MRI

Abstract: Truncated singular value decomposition (TSVD) is an effective method for the deconvolution of dynamic contrast enhanced (DCE) MRI. Two robust methods for the selection of the truncation threshold on a pixel-by-pixel basis--generalized cross validation (GCV) and the L-curve criterion (LCC)--were optimized and compared to paradigms in the literature. GCV and LCC were found to perform optimally when applied with a smooth version of TSVD, known as standard form Tikhonov regularization (SFTR). The methods lead to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
66
0
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(73 citation statements)
references
References 24 publications
6
66
0
1
Order By: Relevance
“…Neglecting dispersion is known to underestimate perfusion (14,15). The magnitude of this error is significant in stroke (16), but with the present protocol it is difficult to estimate for the kidney.…”
Section: Quantification Of Rrbfmentioning
confidence: 93%
“…Neglecting dispersion is known to underestimate perfusion (14,15). The magnitude of this error is significant in stroke (16), but with the present protocol it is difficult to estimate for the kidney.…”
Section: Quantification Of Rrbfmentioning
confidence: 93%
“…The modeling approach may also have a numerical advantage, because it constrains the number of degrees of freedom in the solution. Unconstrained model-free deconvolution is known to suffer from from low accuracy when the noise level is high (36). In (29) constraints are imposed by a polynomial representation of the residue function, which may be expected to improve accuracy and/or precision.…”
Section: Tracer Kinetic Modelingmentioning
confidence: 99%
“…Also, the method combines two tracer-kinetic approaches with contradictory assumptions (a one-compartment model and a model-free analysis), prior knowledge is required regarding the intactness of the BBB, and a one-compartment model may not fit tumor data with large blood volumes. Finally, a modelfree analysis produces severe CBF errors in data with low SNR (36), though the error may be reduced by introducing appropriate constraints in the solution (29).…”
mentioning
confidence: 99%
“…The 10% threshold, however, leads to a larger standard deviation, especially in white matter [29] at lower SNRs, and a higher cut-off value is normally preferable. Sourbron et al [114,115] compared two methods of threshold determination in the SVD deconvolution, namely the L-curve criterion and generalised cross-validation. They concluded that improved image contrast and increased sensitivity to pathology were obtained with both techniques compared with the use of a fixed threshold or a threshold based on SNR C .…”
Section: Model-independent Deconvolutionmentioning
confidence: 99%